The Role of Women in the Sustainable Development Goals (SDGs) Through Village Action Plans/Rencana Aksi Desa (RADes) - Aura, Fanisa; La Mun, Shaw (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Women play a crucial role in accelerating the achievement of the Sustainable Development Goals, particularly SDG 5, which focuses on gender equality. At the village level, women's participation in planning and policy formulation through the Village Action Plan (RADes). This research employs a descriptive-analytical method, collecting data from literature, policies, regulations, statistical reports, and studies related to women's empowerment and the implementation of the SDGs in the village. The results show that women make a significant contribution to village development achievements, including improvements in the quality of human resources, family welfare, and environmental sustainability. However, limited representation of women in decision-making forums, gender-biased social norms, budget planning that is not fully gender responsive, and limited disaggregated data are still obstacles. The Village SDGs, the Women-Friendly and Child-Caring Village (DRPPA) program, and RADes demonstrate positive developments in expanding women's leadership and promoting peaceful, gender-equitable village governance. Therefore, strengthening gender mainstreaming, capacity building, institutional support, and monitoring mechanisms are needed to ensure women's transformative role in sustainable development at the village level.